2005
DOI: 10.1177/154405910508400805
|View full text |Cite
|
Sign up to set email alerts
|

Tuftelin, Mutans Streptococci, and Dental Caries Susceptibility

Abstract: The purpose of this study was to identify genetic factors that contribute to dental caries susceptibility, either alone or in combination with environmental factors. Dental examinations were performed and buccal swab samples collected from 3- to 5-year-old children with at least 4 surfaces of decay, or with no evidence of decay. SNP assays for each of 6 candidate genes were performed for all cases and controls. Chi-square analysis and regression analysis were used for the evaluation of individual gene effects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
132
1
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 17 publications
5
132
1
13
Order By: Relevance
“…5 There were also no associations between amelogenin genetic variants and dental caries experience in other studies performed on Polish, French, Caucasian, and Japanese populations. [6][7][8]12 However, studied SNPs for AMELX gene and the age of children were different from those chosen for our study, also the studied populations were heterogeneous regarding demographic origins and cultural diversity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 There were also no associations between amelogenin genetic variants and dental caries experience in other studies performed on Polish, French, Caucasian, and Japanese populations. [6][7][8]12 However, studied SNPs for AMELX gene and the age of children were different from those chosen for our study, also the studied populations were heterogeneous regarding demographic origins and cultural diversity.…”
Section: Discussionmentioning
confidence: 99%
“…21 Abbasoğlu et al, Deeley et al and Slayton et al did not find association between AMBN genetic variants and caries experience in Turkish, Guatemalan-Mayan and mixed populations, respectively, although Slayton et al noticed that out of the children who participated in the study, Caucasian children had the greatest severity of the disease. 5,7,11 On the other hand, Patir et al observed an overrepresentation of the minor T allele in rs34538475 in caries experienced individuals in comparison to controls, regardless of the stage of the disease. 4 In our study, however, we observed an opposite association, as both the minor T allele (p < 0.0001) and the minor TT homozygote (p < 0.0001) were overrepresented in controls in comparison to cases with caries, which supported the T allele as a protective variant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a disease as widespread and costly as childhood dental caries, surprisingly few studies of specific genetic loci have been reported. Notable associated genes from candidate gene studies include tuftelin (via an environmental interaction) (Slayton et al, 2005), ameloblastin (Deeley et al, 2008) (both involved in tooth enamel composition), and taste genes (Wendell et al, 2010); however, these findings have not been rigorously explored in replication samples. The current lack of understanding regarding the genetic factors leading to dental caries and the paucity of active research in this area showcase the urgent need for more comprehensive investigation of the genetic variants associated with disease.…”
Section: Introduction Tmentioning
confidence: 99%